2021
DOI: 10.3389/fpsyg.2021.767079
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Students' Autonomy and Engagement in EFL Classroom Through Proximal Classroom Factors: Autonomy-Supportive Behaviors and Student-Teacher Relationships

Abstract: Language learning achievement depends on student engagement which is at the center of attention these days. To assist students to become autonomous and independent learners, providing a social and supportive context is beneficial through autonomy-supportive and interaction. When learners are given the freedom to make choices about their education, they are likely to feel more enthusiastic and engaged. Moreover, learners' academic and social practices are largely influenced by educators, who play a major role a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 71 publications
2
14
0
3
Order By: Relevance
“…CTS, with its step-by-step guidance and clear explanations, potentially lowered the occurrences of difficulties, preventing learners from feeling overwhelmed or lost when encountering problems, which in turn, bolstered their emotional engagement. These findings align with previous research highlighting that effective scaffolding and suitable guidance can enhance learners’ emotional engagement (Chen et al, 2020b; Han, 2021; Lee & Hannafin, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…CTS, with its step-by-step guidance and clear explanations, potentially lowered the occurrences of difficulties, preventing learners from feeling overwhelmed or lost when encountering problems, which in turn, bolstered their emotional engagement. These findings align with previous research highlighting that effective scaffolding and suitable guidance can enhance learners’ emotional engagement (Chen et al, 2020b; Han, 2021; Lee & Hannafin, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…It can improve students' motivation to learn and increase their efforts to succeed, which corresponds with studies that apply a flipped classroom approach to facilitate autonomous behavior (Kusurkar & Croiset, 2015;Torbergsen et al, 2023). Han (2021) and Hernández et al (2022) found that instructor support of students' autonomy and providing appropriate feedback on their autonomy could increase students' self-confidence about their current education and future professional roles in the workplace. Faculty members should thus trust and support their students' ability to complete tasks and offer alternatives when needed to foster their success.…”
Section: Discussionmentioning
confidence: 68%
“…Han (2021) and Hernández et al (2022) found that instructor support of students' autonomy and providing appropriate feedback on their autonomy could increase students' self‐confidence about their current education and future professional roles in the workplace. Faculty members should thus trust and support their students' ability to complete tasks and offer alternatives when needed to foster their success.…”
Section: Discussionmentioning
confidence: 99%
“…The great majority of the research literature linked with the subject of language teaching identifies teacher autonomy as a component of an individual's ability to monitor his or her own professional development (Skaalvik et al, 2014). Language TA is encompassed and practiced in their adaptability to figure out how to deal with internal and external restrictions for the advantages of language learning (Han, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%